High-wear-resistance seamless steel tube material and preparation method thereof
The material's wear resistance and corrosion resistance are solved by using powder coatings containing epoxy resin, furfurethane modified polyepoxysuccinic acid and fluorenyl modified polyethylene glycol monoallyl ether on seamless steel pipe materials. and the problem of insufficient antistatic ability, higher wear resistance, corrosion resistance and safety are achieved.
Patent Information
- Application Number
- CN202411481556.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-11
AI Technical Summary
The existing seamless steel pipe materials have insufficient wear resistance and corrosion resistance during use, and do not have antistatic ability, which poses safety hazards.
Using a powder coating, including epoxy resin, furfurethane modified polyepoxy succinic acid and fluorenyl modified polyethylene glycol monoallyl ether, it is sprayed on a seamless steel pipe substrate through electrostatic spraying technology. The surface is formed to form a strong coating to improve wear and corrosion resistance, and enhance antistatic capacity by introducing quaternary ammonium groups.
It significantly improves the wear resistance, corrosion resistance and anti-static ability of seamless steel pipe materials, making them less likely to wear when used in various environments, have high safety, and extends their service life.
Smart Images

Figure CN119410225A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel pipe material preparation, and in particular to a high wear-resistant seamless steel pipe material and a preparation method thereof. Background Art
[0002] Seamless steel pipe material is a material widely used in the fields of petroleum, chemical industry, electric power, construction, machinery manufacturing and geological drilling. Due to its wide use, seamless steel pipe material not only needs to withstand greater mechanical stress and wear, but also often needs to contact various corrosive media, such as acid, alkali, salt, etc. These corrosive media will not only cause rust on the surface of seamless steel pipe materials, but will also seriously cause stress corrosion cracking and other problems, threatening the stability of the use of seamless steel pipe materials. In the fields of petroleum, chemical industry and geological drilling, seamless steel pipe materials need to have good anti-static ability to avoid the safety hazards caused by electric sparks generated by static electricity.
[0003] At present, the corrosion resistance and wear resistance of seamless steel pipe materials are mainly achieved through two ways: alloying design and surface treatment. Alloying design is to add alloy elements during the preparation of steel to form a passivation film, which effectively enhances corrosion resistance and wear resistance. However, the process is relatively complicated and it is difficult to achieve antistatic effect on the surface of seamless steel pipe materials. The surface treatment process is relatively simple. For example, the patent with announcement number CN109136851B discloses a stainless steel pipe anti-corrosion post-treatment process. By applying a rust inhibitor on the surface of the stainless steel pipe, the corrosion resistance of the stainless steel pipe is achieved, so that it has a good service life. The process is simple, but the patent does not perform antistatic treatment on the surface of the steel pipe, which limits the use of this type of steel pipe. Summary of the invention
[0004] The purpose of the present invention is to provide a highly wear-resistant seamless steel pipe material and a preparation method thereof, which solves the problem that the surface wear resistance and corrosion resistance of ordinary steel pipe materials are average and difficult to use for a long time, and the surface of ordinary steel pipe materials is not anti-static and there are safety hazards when used in special environments.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A highly wear-resistant seamless steel pipe material comprises a seamless steel pipe substrate and a powder coating sprayed on the surface of the seamless steel pipe substrate; the powder coating comprises the following raw materials in parts by weight: 80-100 parts of epoxy resin, 20-25 parts of furfuryl-modified polyepoxysuccinic acid, 12-15 parts of fluorene-modified polyethylene glycol monoallyl ether, 6-8 parts of filler, 3-5 parts of defoamer, 2-3 parts of antioxidant, and 2-5 parts of leveling agent.
[0007] Furthermore, the epoxy resin is any one of bisphenol A epoxy resin and bisphenol F epoxy resin; the filler is any one of nano calcium carbonate, nano silicon dioxide, and mica powder; the defoamer is any one of dimethyl silicone oil and polyoxyethylene defoamer; the antioxidant is any one of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol; the leveling agent is any one of polydimethylsiloxane and polybutyl acrylate.
[0008] Furthermore, the preparation method of the furfuryl-modified polyepoxysuccinic acid comprises the following steps:
[0009] S1: placing polyepoxysuccinic acid in deionized water, mixing and stirring thoroughly, adding 5-bromo-2-furoic acid methyl ester and an accelerator, heating to 55-65° C. for reaction for 2-4 hours, and after the reaction, filtering and drying the product to obtain a modified polyepoxysuccinic acid;
[0010] S2: Place the modified polyepoxysuccinic acid and 2-aminoethanethiol in N,N-dimethylformamide, introduce nitrogen, add a composite catalyst, raise the temperature to 60-70°C and react for 3-5 hours, remove the solvent by rotary evaporation, and collect the product to obtain furfuryl-modified polyepoxysuccinic acid.
[0011] In this scheme, under the action of a promoter, the hydroxyl group in the structure of polyepoxysuccinic acid undergoes a substitution reaction with the active bromine in the structure of 5-bromo-2-furoic acid methyl ester to obtain modified polyepoxysuccinic acid, and then under the action of a composite catalyst, the carboxyl group in the structure of modified polyepoxysuccinic acid reacts with the amino group in the structure of 2-aminoethanethiol to obtain furfuryl-modified polyepoxysuccinic acid. The furfuryl-modified polyepoxysuccinic acid uses polyepoxysuccinic acid as a polymer skeleton, and itself has the properties of salt resistance and acid and alkali corrosion resistance. The corrosion-resistant furfuryl group is introduced into its polymer skeleton in a chemically bonded manner, which can further enhance its corrosion resistance. By introducing a thiol group into the structure of the modified polyepoxysuccinic acid, the prepared furfuryl-modified polyepoxysuccinic acid can be used as a curing agent for epoxy resin coatings, thereby enhancing the cross-linking density of the coatings. The prepared furfuryl-modified polyepoxysuccinic acid can be sprayed on the surface of a seamless steel pipe substrate, so that the prepared seamless steel pipe material can meet the use requirements in corrosive media and have a long service life.
[0012] Furthermore, in step S1, the accelerator is pyridine.
[0013] Furthermore, in step S2, the composite catalyst is dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 0.8-2:0.2-0.5.
[0014] Furthermore, the preparation method of the fluorenyl-modified polyethylene glycol monoallyl ether comprises the following steps:
[0015] SS1: Place polyethylene glycol monoallyl ether in toluene, add 2-aminofluorene and triethylamine, heat to 70-80°C and stir thoroughly for 2.5-5h, remove the solvent by distillation under reduced pressure, and collect the product to obtain modified polyethylene glycol monoallyl ether;
[0016] SS2: Place the modified polyethylene glycol monoallyl ether in dimethyl sulfoxide, add 2,3-epoxypropyltrimethylammonium chloride and tetrabutylammonium bromide, heat to react, collect the product after rotary evaporation, and obtain fluorene-modified polyethylene glycol monoallyl ether.
[0017] In this scheme, under the action of triethylamine, the double bond in the polyethylene glycol monoallyl ether structure and the amino group in the 2-aminofluorene structure undergo Michael addition reaction to obtain modified polyethylene glycol monoallyl ether, and then under the action of tetrabutylammonium bromide, the hydroxyl group in the modified polyethylene glycol monoallyl ether structure and the epoxy group in the 2,3-epoxypropyltrimethylammonium chloride structure undergo ring-opening reaction to obtain fluorene-modified polyethylene glycol monoallyl ether. The fluorene-modified polyethylene glycol monoallyl ether uses polyethylene glycol monoallyl ether as a polymer skeleton, and has a large number of ether bonds in its structure, which can enhance the adhesion between the coating and the surface of the steel pipe material. The fluorene group is introduced into its structure in a chemically bonded manner, so that the prepared coating has excellent wear resistance. At the same time, the introduction of quaternary ammonium groups in its structure can give the coating antistatic ability. The fluorene-modified polyethylene glycol monoallyl ether has hydroxyl groups in its structure, which can participate in the curing process of the epoxy resin coating. It has great compatibility and can give full play to the wear resistance and antistatic ability. It is sprayed on the surface of the seamless steel pipe substrate, so that the prepared seamless steel pipe material has excellent wear resistance and antistatic ability, making it not easy to wear during use, highly safe, and can meet the use requirements in various environments.
[0018] Furthermore, in step SS1, the molecular weight of the polyethylene glycol monoallyl ether is 2000-5000.
[0019] Furthermore, in step SS2, the temperature of the temperature-raising reaction is 85-100° C., and the time is 5-6 hours.
[0020] A method for preparing a highly wear-resistant seamless steel pipe material comprises the following steps:
[0021] Step 1, placing epoxy resin, furfuryl-modified polyepoxysuccinic acid, fluorene-modified polyethylene glycol monoallyl ether, filler, defoamer, antioxidant, and leveling agent in a high-speed mixer, stirring at 500-600r / min for 15-20min, fully mixing, adding to a twin-screw extruder, setting the extruder discharge temperature to 140-160°C, the speed to 350-550r / min, melt-extruded and then tabletted, crushed with a high-speed crusher and sieved through a 150-200 mesh sieve to obtain a powder coating;
[0022] Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. After rust removal, preheat the steel pipe at a temperature of 160-180°C, and use electrostatic spraying to spray powder coating on the surface of the seamless steel pipe. Set the spraying pressure to 70-80kV, the powder spraying amount to 150-180g / min, and the coating thickness to 380-420μm;
[0023] Step 3: solidify the sprayed seamless steel pipe at 180-200°C for 1-1.5 minutes, spray the mark after cooling, and obtain the seamless steel pipe material.
[0024] Furthermore, in step 2, the rust removal grade of the shot blasting and sand blasting is Sa2.5.
[0025] Beneficial effects of the present invention:
[0026] The present invention prepares furfuryl-modified polyepoxysuccinic acid and fluorene-modified polyethylene glycol monoallyl ether and participates in the preparation process of powder coating, so that the prepared powder coating has excellent corrosion resistance, wear resistance, antistatic ability and adhesion, and sprays it on the surface of seamless steel pipe substrate, so that the finally prepared seamless steel pipe material can stably exist in corrosive medium, is not easy to wear and has antistatic ability, can meet the use requirements in various environments, and has a long service life.
[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0029] Figure 1 The zeta potential diagram of the modified polyethylene glycol monoallyl ether and the fluorene-modified polyethylene glycol monoallyl ether of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The preparation methods of the furfuryl-modified epoxysuccinic acid and fluorenyl-modified polyethylene glycol monoallyl ether in the following examples and comparative examples of the present invention are as follows:
[0032] 1. Preparation of furfuryl-modified polyepoxysuccinic acid
[0033] S1: 3.2 g of polyepoxysuccinic acid was placed in 60 ml of deionized water, and after sufficient mixing and stirring, 2 g of 5-bromo-2-furoic acid methyl ester and 0.05 g of pyridine were added, and the temperature was raised to 55° C. for reaction for 2 h. After the reaction, the product was filtered and dried to obtain a modified polyepoxysuccinic acid;
[0034] S2: 3.5 g of modified polyepoxysuccinic acid and 2.5 g of 2-aminoethanethiol are placed in 80 ml of N,N-dimethylformamide, nitrogen is introduced, 0.8 g of dicyclohexylcarbodiimide and 0.2 g of 4-dimethylaminopyridine are added, the temperature is raised to 60°C and the reaction is carried out for 3 h. The solvent is removed by rotary evaporation, and the product is collected to obtain furfuryl-modified polyepoxysuccinic acid.
[0035] The nitrogen and sulfur elements in modified polyepoxysuccinic acid and furfuryl-modified polyepoxysuccinic acid were analyzed using a Thermo element analyzer. The results showed that modified polyepoxysuccinic acid did not contain nitrogen and sulfur elements; the nitrogen content in furfuryl-modified polyepoxysuccinic acid was 3.2%, and the sulfur content was 4.9%; the appearance of nitrogen and sulfur elements was due to the reaction between modified polyepoxysuccinic acid and the amino group in the 2-aminoethanethiol structure.
[0036] 2. Preparation of fluorene-modified polyethylene glycol monoallyl ether
[0037] SS1: 2.8 g of polyethylene glycol monoallyl ether with a molecular weight of 2000 was placed in 50 ml of toluene, 2 g of 2-aminofluorene and 0.4 g of triethylamine were added, the temperature was raised to 70°C and stirred for 2.5 h, the solvent was removed by distillation under reduced pressure, and the product was collected to obtain modified polyethylene glycol monoallyl ether;
[0038] SS2: Place 3.5 g of modified polyethylene glycol monoallyl ether in 80 ml of dimethyl sulfoxide, add 3 g of 2,3-epoxypropyltrimethylammonium chloride and 0.3 g of tetrabutylammonium bromide, heat to 85 °C and react for 5 h. Collect the product after rotary evaporation to obtain fluorenyl-modified polyethylene glycol monoallyl ether.
[0039] The potential values of modified polyethylene glycol monoallyl ether and fluorene-modified polyethylene glycol monoallyl ether were detected using a JS94H2 zeta potential meter. Figure 1 It can be seen that the potential value of modified polyethylene glycol monoallyl ether is -4.1mv, which is a negative value; the potential value of fluorenyl-modified polyethylene glycol monoallyl ether is 2.6mv, which is a positive value; the potential value has changed significantly, which is due to the positively charged quaternary ammonium group in the structure of fluorenyl-modified polyethylene glycol monoallyl ether.
[0040] Example 1
[0041] Preparation of seamless steel pipe materials
[0042] Step 1, 80 parts of bisphenol A epoxy resin, 20 parts of furfuryl-modified polyepoxysuccinic acid, 12 parts of fluorenyl-modified polyethylene glycol monoallyl ether, 6 parts of nano-calcium carbonate, 3 parts of dimethyl silicone oil, 2 parts of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, and 2 parts of polydimethylsiloxane are placed in a high-speed mixer, stirred at 500 r / min for 15 minutes, fully mixed, added to a twin-screw extruder, set the extruder discharge temperature to 140°C, the speed to 350 r / min, melt-extruded and then tableted, crushed with a high-speed crusher and sieved through a 150-mesh sieve to obtain a powder coating;
[0043] Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. The rust removal level is Sa2.5. After the rust removal is completed, the steel pipe is preheated at a preheating temperature of 160°C. The powder coating is sprayed on the surface of the seamless steel pipe by electrostatic spraying. The spraying pressure is set to 70kV, the powder spraying amount is 150g / min, and the coating thickness is 380μm.
[0044] Step 3: solidify the sprayed seamless steel pipe at 180°C for 1 minute, spray the mark after cooling, and obtain the seamless steel pipe material.
[0045] Example 2
[0046] Preparation of seamless steel pipe materials
[0047] Step 1, 90 parts of bisphenol A epoxy resin, 22 parts of furfuryl-modified polyepoxysuccinic acid, 14 parts of fluorenyl-modified polyethylene glycol monoallyl ether, 7 parts of nano-silica, 4 parts of polyoxyethylene defoamer, 2.5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 3 parts of polybutyl acrylate are placed in a high-speed mixer, stirred at 550 r / min for 18 min, fully mixed, added to a twin-screw extruder, set the extruder discharge temperature to 150° C., the speed to 400 r / min, melt-extruded and then tableted, crushed with a high-speed crusher and sieved through a 180-mesh sieve to obtain a powder coating;
[0048] Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. The rust removal level is Sa2.5. After rust removal, preheat the steel pipe at a preheating temperature of 170°C. Use electrostatic spraying to spray powder coating on the surface of the seamless steel pipe. Set the spraying pressure to 75kV, the powder spraying amount to 160g / min, and the coating thickness to 400μm.
[0049] Step 3: solidify the sprayed seamless steel pipe at 190°C for 1.2 minutes, spray the mark after cooling, and obtain the seamless steel pipe material.
[0050] Example 3
[0051] Preparation of seamless steel pipe materials
[0052] Step 1, 100 parts of bisphenol F epoxy resin, 25 parts of furfuryl-modified polyepoxysuccinic acid, 15 parts of fluorenyl-modified polyethylene glycol monoallyl ether, 8 parts of mica powder, 5 parts of dimethyl silicone oil, 3 parts of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, and 5 parts of polybutyl acrylate are placed in a high-speed mixer, stirred at 600 r / min for 20 min, fully mixed, added to a twin-screw extruder, the extruder discharge temperature is set to 160° C., the speed is 550 r / min, melt extruded and then tableted, crushed with a high-speed crusher and passed through a 200-mesh sieve to obtain a powder coating;
[0053] Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. The rust removal grade is Sa2.5. After the rust removal is completed, the steel pipe is preheated at a preheating temperature of 180°C. The powder coating is sprayed on the surface of the seamless steel pipe by electrostatic spraying. The spraying pressure is set to 80kV, the powder spraying amount is 180g / min, and the coating thickness is 420μm.
[0054] Step 3: solidify the sprayed seamless steel pipe at 200°C for 1.5 minutes, spray the mark after cooling, and obtain the seamless steel pipe material.
[0055] Comparative Example 1
[0056] Preparation of seamless steel pipe materials
[0057] Step 1, 90 parts of bisphenol A epoxy resin, 22 parts of ethylenediamine, 14 parts of fluorene-modified polyethylene glycol monoallyl ether, 7 parts of nano-silicon dioxide, 4 parts of polyoxyethylene defoamer, 2.5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 3 parts of polybutyl acrylate are placed in a high-speed mixer, stirred at 550 r / min for 18 minutes, fully mixed, added to a twin-screw extruder, set the extruder discharge temperature to 150°C, the speed to 400 r / min, melt-extruded and then tableted, crushed with a high-speed crusher and passed through a 180-mesh sieve to obtain a powder coating;
[0058] Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. The rust removal level is Sa2.5. After rust removal, preheat the steel pipe at a preheating temperature of 170°C. Use electrostatic spraying to spray powder coating on the surface of the seamless steel pipe. Set the spraying pressure to 75kV, the powder spraying amount to 160g / min, and the coating thickness to 400μm.
[0059] Step 3: solidify the sprayed seamless steel pipe at 190°C for 1.2 minutes, spray the mark after cooling, and obtain the seamless steel pipe material.
[0060] Comparative Example 2
[0061] Preparation of seamless steel pipe materials
[0062] Step 1, 90 parts of bisphenol A epoxy resin, 22 parts of furfuryl-modified polyepoxysuccinic acid, 7 parts of nano-silica, 4 parts of polyoxyethylene defoamer, 2.5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 3 parts of polybutyl acrylate are placed in a high-speed mixer, stirred at 550 r / min for 18 minutes, fully mixed, added to a twin-screw extruder, set the extruder discharge temperature to 150°C, the speed to 400 r / min, melt-extruded and then tableted, crushed with a high-speed crusher and passed through a 180-mesh sieve to obtain a powder coating;
[0063] Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. The rust removal level is Sa2.5. After rust removal, preheat the steel pipe at a preheating temperature of 170°C. Use electrostatic spraying to spray powder coating on the surface of the seamless steel pipe. Set the spraying pressure to 75kV, the powder spraying amount to 160g / min, and the coating thickness to 400μm.
[0064] Step 3: solidify the sprayed seamless steel pipe at 190°C for 1.2 minutes, spray the mark after cooling, and obtain the seamless steel pipe material.
[0065] Comparative Example 3
[0066] Preparation of seamless steel pipe materials
[0067] Step 1, 90 parts of bisphenol A epoxy resin, 22 parts of furfuryl-modified polyepoxysuccinic acid, 14 parts of modified polyethylene glycol monoallyl ether, 7 parts of nano-silicon dioxide, 4 parts of polyoxyethylene defoamer, 2.5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 3 parts of polybutyl acrylate are placed in a high-speed mixer, stirred at 550 r / min for 18 minutes, fully mixed, added to a twin-screw extruder, set the extruder discharge temperature to 150°C, the speed to 400 r / min, melt-extruded and then tableted, crushed with a high-speed crusher and passed through a 180-mesh sieve to obtain a powder coating;
[0068] Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. The rust removal level is Sa2.5. After rust removal, preheat the steel pipe at a preheating temperature of 170°C. Use electrostatic spraying to spray powder coating on the surface of the seamless steel pipe. Set the spraying pressure to 75kV, the powder spraying amount to 160g / min, and the coating thickness to 400μm.
[0069] Step 3: solidify the sprayed seamless steel pipe at 190°C for 1.2 minutes, spray the mark after cooling, and obtain the seamless steel pipe material.
[0070] Comparative Example 4
[0071] Preparation of seamless steel pipe materials
[0072] Step 1, 90 parts of bisphenol A epoxy resin, 22 parts of furfuryl-modified polyepoxysuccinic acid, 14 parts of polyethylene glycol monoallyl ether, 7 parts of nano-silicon dioxide, 4 parts of polyoxyethylene defoamer, 2.5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 3 parts of polybutyl acrylate are placed in a high-speed mixer, stirred at 550 r / min for 18 minutes, fully mixed, added to a twin-screw extruder, the extruder discharge temperature is set to 150° C., the speed is 400 r / min, melt-extruded and then tableted, crushed with a high-speed crusher and passed through a 180-mesh sieve to obtain a powder coating;
[0073] Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. The rust removal level is Sa2.5. After rust removal, preheat the steel pipe at a preheating temperature of 170°C. Use electrostatic spraying to spray powder coating on the surface of the seamless steel pipe. Set the spraying pressure to 75kV, the powder spraying amount to 160g / min, and the coating thickness to 400μm.
[0074] Step 3: solidify the sprayed seamless steel pipe at 190°C for 1.2 minutes, spray the mark after cooling, and obtain the seamless steel pipe material.
[0075] Performance Testing
[0076] The powder coatings prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 4 were sprayed on a steel plate by electrostatic spraying, and samples meeting the specifications were prepared after curing. The samples were subjected to a wear test for 10 min using an MMW-1G universal friction and wear tester under a load of 100 N and a rotation speed of 100 r / min. The mass of the sample before and after wear was weighed using an electronic balance with an accuracy of 0.1 mg. The wear value was calculated according to the following formula: wear value = mass before wear - mass after wear. The smaller the wear value, the stronger the wear resistance of the sample. The resistance value of the sample was tested at a voltage of 100 V using a zc36 high resistance meter to determine the antistatic ability of the sample. The adhesion grade of the sample was tested according to the reference standard GB / T1727-2021 to determine the adhesion strength of the sample. The salt spray resistance of the sample was tested according to the reference standard GB / T1771-2007 to determine the corrosion resistance of the sample. The specific test results are shown in the table below:
[0077] Wear value / mg Resistance value / Ω Adhesion grade Salt spray resistance / h Example 1 0.33 <![CDATA[2.2×10 6 ]]> 0 2000 Example 2 0.29 <![CDATA[1.6×10 6 ]]> 0 2100 Example 3 0.30 <![CDATA[1.9×10 6 ]]> 0 2000 Comparative Example 1 0.65 <![CDATA[3.1×10 6 ]]> 1 900 Comparative Example 2 1.23 <![CDATA[4.5×10 11 ]]> 1 1700 Comparative Example 3 0.42 <![CDATA[5.8×10 11 ]]> 0 1800 Comparative Example 4 0.71 <![CDATA[1.3×10 12 ]]> 0 1700
[0078] As can be seen from the above table, the samples prepared in Examples 1 to 3 all have excellent wear resistance, antistatic ability, adhesion and corrosion resistance. The sample prepared in Comparative Example 1 does not add furfuryl-modified polyepoxysuccinic acid, uses a common curing agent, and has poor corrosion resistance. However, since fluorenyl-modified polyethylene glycol monoallyl ether is added thereto, the sample has strong wear resistance and antistatic ability, and has good adhesion. In the sample prepared in Comparative Example 2, fluorenyl-modified polyethylene glycol monoallyl ether is not added. Therefore, the wear resistance is general and the antistatic ability is poor, but furfuryl-modified polyepoxysuccinic acid is added therein, and the corrosion resistance is good. The sample prepared in Example 3 adds furfuryl-modified polyepoxysuccinic acid and modified polyethylene glycol monoallyl ether, and has good wear resistance, strong corrosion resistance, and excellent adhesion, but poor antistatic ability. The sample prepared in Example 4 adds furfuryl-modified polyepoxysuccinic acid and polyethylene glycol monoallyl ether, and has good corrosion resistance and adhesion, but poor wear resistance and antistatic ability.
[0079] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0080] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A highly wear-resistant seamless steel pipe material, characterized in that: It includes a seamless steel pipe substrate and a powder coating sprayed on the surface of the seamless steel pipe substrate; the powder coating includes the following raw materials in parts by weight: 80-100 parts of epoxy resin, 20-25 parts of furfuryl-modified polyepoxysuccinic acid, 12-15 parts of fluorene-modified polyethylene glycol monoallyl ether, 6-8 parts of filler, 3-5 parts of defoamer, 2-3 parts of antioxidant, and 2-5 parts of leveling agent.
2. A highly wear-resistant seamless steel pipe material according to claim 1, characterized in that: The epoxy resin is any one of bisphenol A epoxy resin and bisphenol F epoxy resin; the filler is any one of nano calcium carbonate, nano silicon dioxide, and mica powder; the defoamer is any one of dimethyl silicone oil and polyoxyethylene defoamer; the antioxidant is any one of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol; the leveling agent is any one of polydimethylsiloxane and polybutyl acrylate.
3. A highly wear-resistant seamless steel pipe material according to claim 1, characterized in that: The preparation method of the furfuryl-modified polyepoxysuccinic acid comprises the following steps: S1: placing polyepoxysuccinic acid in deionized water, mixing and stirring thoroughly, adding 5-bromo-2-furoic acid methyl ester and an accelerator, heating to 55-65° C. for reaction for 2-4 hours, and after the reaction, filtering and drying the product to obtain a modified polyepoxysuccinic acid; S2: Place the modified polyepoxysuccinic acid and 2-aminoethanethiol in N,N-dimethylformamide, introduce nitrogen, add a composite catalyst, raise the temperature to 60-70°C and react for 3-5 hours, remove the solvent by rotary evaporation, and collect the product to obtain furfuryl-modified polyepoxysuccinic acid.
4. A highly wear-resistant seamless steel pipe material according to claim 3, characterized in that: In step S1, the accelerator is pyridine.
5. The high wear-resistant seamless steel pipe material according to claim 3, characterized in that: In step S2, the composite catalyst is dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 0.8-2:0.2-0.
5.
6. The high wear-resistant seamless steel pipe material according to claim 1, characterized in that: The preparation method of the fluorenyl-modified polyethylene glycol monoallyl ether comprises the following steps: SS1: Place polyethylene glycol monoallyl ether in toluene, add 2-aminofluorene and triethylamine, heat to 70-80°C and stir thoroughly for 2.5-5h, remove the solvent by distillation under reduced pressure, and collect the product to obtain modified polyethylene glycol monoallyl ether; SS2: Place the modified polyethylene glycol monoallyl ether in dimethyl sulfoxide, add 2,3-epoxypropyltrimethylammonium chloride and tetrabutylammonium bromide, heat to react, collect the product after rotary evaporation, and obtain fluorene-modified polyethylene glycol monoallyl ether.
7. A highly wear-resistant seamless steel pipe material according to claim 6, characterized in that: In step SS1, the molecular weight of the polyethylene glycol monoallyl ether is 2000-5000.
8. The high wear-resistant seamless steel pipe material according to claim 6, characterized in that: In step SS2, the temperature of the temperature-raising reaction is 85-100° C. and the time is 5-6 hours.
9. A method for preparing a high wear-resistant seamless steel pipe material as claimed in claim 1, characterized in that: The following steps are involved: Step 1, placing epoxy resin, furfuryl-modified polyepoxysuccinic acid, fluorene-modified polyethylene glycol monoallyl ether, filler, defoamer, antioxidant, and leveling agent in a high-speed mixer, stirring at 500-600r / min for 15-20min, fully mixing, adding to a twin-screw extruder, setting the extruder discharge temperature to 140-160°C, the speed to 350-550r / min, melt-extruded and then tabletted, crushed with a high-speed crusher and sieved through a 150-200 mesh sieve to obtain a powder coating; Step 2: Use acetone and clean water to clean the seamless steel pipe substrate in turn, and then perform shot blasting and sand blasting to remove rust after drying. After rust removal, preheat the steel pipe at a temperature of 160-180°C, and use electrostatic spraying to spray powder coating on the surface of the seamless steel pipe. Set the spraying pressure to 70-80kV, the powder spraying amount to 150-180g / min, and the coating thickness to 380-420μm; Step 3: solidify the sprayed seamless steel pipe at 180-200°C for 1-1.5 minutes, spray the mark after cooling, and obtain the seamless steel pipe material.
10. The method for preparing a highly wear-resistant seamless steel pipe material according to claim 9, characterized in that: In step 2, the rust removal grade of the shot blasting and sand blasting is Sa2.5.
Citation Information
Patent Citations
Post-treatment process for corrosion resistance of stainless steel pipes
CN109136851B